Studi Eksplorasi Pengaturan Kerja Fleksibel Terhadap Keterlekatan Pekerja - Anugrah, Rut Gloria; Lagandhy, Langga (Syntax Literate, 2026)
This study explores the implementation of Flexible Working Arrangements (FWA) on employee engagement within a multi-generational workforce context in Indonesia. The research employs a qualitative approach through semi-structured interviews with 14 respondents comprising policy makers and employees from various generations (Generation X, Millennials, and Z) at a tech start-up company. The findings indicate that FWA, initially implemented as a response to the COVID-19 pandemic, remains relevant as a modern business strategy to enhance efficiency and productivity. Key benefits identified include improved work-life balance, cost savings in transportation and operational expenses, enhanced work morale, and better productivity. Generation Z demonstrates the most positive response to this policy, making FWA a crucial tool for attracting and retaining young talent. However, the research also identifies several challenges such as policy misuse by some employees and miscommunication in team coordination, particularly in complex projects. The study concludes that FWA effectiveness depends on clear and transparent policy definitions, effective two-way communication between managers and employees, and strong leadership support. Generational differences influence how work flexibility is utilized, with younger generations tending to use it for individual target focus or socialization time, while older generations leverage it for family responsibilities. This research recommends an inclusive approach in designing FWA policies that meet cross-generational needs to optimally drive employee engagement.